PERFORMANCE ANALYSIS OF A CORPORATE INTRANET ON A NETWORK - Mayta H., Rosmery (2002)
Intranets provide some of the most powerful and economical since the invention of the telephone technologies. Although simple in its architecture, intranets have the potential to change the way people work, learn and process information, reason have had tremendous growth and today almost all companies have a. [1] This paper analyzes the performance of an Intranet on a corporate network (in this case it was considered the network of a bank), through an analysis of usage statistics and measurement techniques and simulation with achieve results at particular level and general level.